Pelanggaran Hak Cipta Oleh Oknum Karyawan PT. TE Pada Pemakaian Perangkat Lunak "Geovia Surpac" Bajakan: Infringement Copyright By TE Company Certain Employee In The Use Of Pirated “Geovia Surpac” Software - Rayi Putri Maheswari; Simona Bustani (Reformasi Hukum Trisakti, 2024)
Article 40 paragraph (1) letter S of Copyright Laws acknowledges that software are protected creations, providing assurance against acts of theft as stipulated in Article 113 of Copyright Law. The issue of study how to protect economic rights of “Geovia Surpac” software copyright holder, which have been violated according to UUHC, and PT. TE preventing action of the pirated software usage in future. This study normative descriptive research, use secondary data from literature and primary data through interview, examined qualitative, concluded with deductive logic. The result and conslusions are shoes copyright grants exclusive rights for creator in the form of economic and moral rights according to Article 4 of the Copyright Law. The violation to economic rights to copyright holder of “Geovia Surpac” software by certain employee of PT. TE breaches Article 113 of the Copyright Law. The resolution agreed upon by both parties is through negotiations for the purchase of “Geovia Surpac” software for one use at market price, release of PT. TE from any related dispute cost, and release from civil or criminal lawsuit.